2000
DOI: 10.3354/meps203215
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the occurrence of early maturing males in the protandrous pandalid shrimp Pandalus latirostris

Abstract: Some Age-0 males of the protandrous pandalid shrimp Pandalus latirostris Rathbun mature in their first year, and the proportion of these early maturing males (EMMs) in a population varies both locally and annually. Two laboratory experiments and 2 field observations were conducted to clarify the factors affecting the occurrence of EMMs. The first experiment showed that EMMs needed to grow fast until the breeding season and began producing sperm at about 14 mm carapace length. Individuals with an AMP (length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…b). Our previous laboratory observations showed that there was little difference in growth between immature and mature individuals at age 0 and between males or females at age 1 (Chiba, Goshima & Mizushima ; Chiba ). We therefore considered our cohort separation procedure to be reasonable for estimating the age groups of age 0, age 1 and age ≥ 2.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…b). Our previous laboratory observations showed that there was little difference in growth between immature and mature individuals at age 0 and between males or females at age 1 (Chiba, Goshima & Mizushima ; Chiba ). We therefore considered our cohort separation procedure to be reasonable for estimating the age groups of age 0, age 1 and age ≥ 2.…”
Section: Methodsmentioning
confidence: 96%
“…However, males that do not change sex at age 2, termed here as postponed‐change males (PCM), are often observed in these populations. Moreover, males at age 0 and females at age 1, termed here as early‐matured males (EMM) and early‐changed females (ECF), respectively, also occur, although their proportions are relatively low (Chiba, Goshima & Mizushima ; Chiba & Goshima ). Such life‐history variations are also common in other species of pandalid shrimps (Bergström ).…”
Section: Methodsmentioning
confidence: 99%
“…The turbidities were produced with kaorin (Kanto Chemical Co. Inc., Tokyo, Japan). In both salinity and turbidity experiments, we maintained treatment water at 18°C, which is a typical temperature in summer 12 at which low salinity and highly turbid water was observed (Ogata, unpubl. data, 2001).…”
mentioning
confidence: 99%
“…To investigate the effects of DO, groups of 20 shrimps with carapace lengths (CL) of 22.5-34.5 mm were randomly chosen and transferred to aquariums (60 cm ¥ 30 cm ¥ 30 cm high) containing filtered seawater (c. 30 practical salinity units [psu]). The water temperature was increased 1∞C per 12 h from ambient temperature until it reached 21∞C, which corresponds to the highest temperature in summer, 12 at which time DO is the lowest in northern Hokkaido. 10 DO was adjusted to either 0.1, 1.0, 2.0 or 8.0 mg-O 2 /L at 21∞C by pumping air for the saturated level and an O 2 /N 2 mixture (Taiyo-Toyo-Sanso Co. Ltd, Osaka, Japan) for the other levels through a plastic lid with an inlet and an outlet.…”
mentioning
confidence: 99%
“…Though transplantation between populations is being planned to sustain shrimp stocks in some populations, this may disturb the natural population structure and genetic diversity of the shrimp, in which genetic differentiation between local populations is probably high. Since the species has no planktonic larval period and establishes discrete habitats exclusively in seagrass areas (Chiba et al 2000), the dispersal ability between local populations would be low. Therefore, local populations would be genetically very different from each other.…”
mentioning
confidence: 99%